Summary and Analysis of Relevant Evidence for Nondrug Nursing Programs in Neonatal Operational Pain Management - Zhuo Yang; Yinan Fu; Yueqi Wang (Emergency Medicine International)
Purpose. To summarize the relevant evidence for nondrug nursing programs in neonatal operational pain management. Methods. Computer search for the literature on neonatal procedural pain from 2015 to 2020 in Up To Date, JBI, NICE, SIGN, RNAO, NGC, PubMed, Cochrane Library, CNKI, and Wanfang database was conducted. All literature works that may meet the inclusion criteria were independently evaluated by two researchers to determine the quality grade of the articles. Results. Finally, 9 literature works were extracted, including 4 guidelines, 3 systematic reviews, and 2 evidence summaries. The relevant contents of the literature were extracted and summarized, and 20 pieces of the best evidence were obtained. Conclusion. Breast feeding, sweetener, Kangaroo mother care, sensory stimulation, nonnutritive sucking, and other nondrug nursing programs can reduce the neonatal operational pain, which has guiding significance in neonatal operational pain management.